Pergeseran Hukum Keluarga di Maroko dari Mudawwanah Tahun 1957-1958 ke Mudawwanah Tahun 2004 - Ali Trigiyatno; Siti Qomariyah; Eko Yuni Aryanto; Salafudin Yusuf; Amat Sulaiman (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2022)
A law being reviewed and amended would not be a strange phenomenon. In Morocco, family law has been changed from the old Mudawwanah to the new Mudawwanah. Even though they belong to the Maliki school of thought, Morocco still wants to take from other schools that they feel are more substantial and beneficial. This article intends to explain the shift in family law provisions in Morocco from the old Mudawwanah, ratified in 1957-58, to the new Mudawwanah, approved in 2004. Despite opposition from various groups, the Mudawwanah al-Usrah in 2004 was successfully ratified and enforced for Moroccan citizens. Many parties, especially gender activists, praised the 2004 Mudawwanah as a progressive family law that cares about gender in Arab countries. There were at least seventeen issues in the 2004 Mudawwanah, which underwent quite fundamental and significant shifts compared to the provisions in the previous Mudawwanah. The new provision seeks to strengthen the rights and position of Moroccan women as well as legal protection and guarantees for children.   Abstrak: Sebuah undang-undang ditinjau dan diamandemen kiranya bukan persoalan aneh lagi. Di Maroko, telah terjadi amandemen hukum keluarga cukup signifikan dari Mudawwanah lama dengan Mudawwanah baru. Walau bermazhab Maliki, namun Maroko tetap mau mengambil dari mazhab lain yang dirasa lebih kuat dan maslahat. Artikel ini hendak menjelaskan pergeseran ketentuan hukum keluarga di Maroko dari Mudawwanah lama yang disahkan tahun 1957-58 dengan Mudawwanah baru yang disahkan tahun 2004. Walau ada penentangan dari berbagai kalangan, namun akhirnya Mudawwanah al-Usrah tahun 2004 berhasil disahkan dan diberlakukan bagi warga negara Maroko. Banyak pihak terutama aktifis jender memuji Mudawwanah tahun 2004 sebagai hukum keluarga yang progresif dan peduli jender untuk ukuran negeri-negeri Arab. Sekurangnya ada tujuh belas isu dalam Mudawwanah tahun 2004 yang mengalami pergeseran cukup mendasar dan signifikan dibanding ketentuan dalam Mudawwanah sebelumnya. Ketentuan baru tersebut pada dasarnya berupaya untuk menguatkan hak-hak dan kedudukan kaum wanita Maroko serta perlindungan dan jaminan hukum bagi anak-anak.